Struggles for provision of palliative care services at the primary healthcare setting in Tanzania; Experiences from health facility in-charges in Dar es Salaam; A qualitative study - Christina Vallen Malichewe; Furahini Yoram; Juda Lyamai; Veronica Mkusa; George Kiwango; Obadia Nyongole; Nathanael Sirili (PLoS ONE, 2026)
Background The rising burden of chronic illnesses due to Communicable Diseases and Non-communicable Diseases has heightened the need for palliative care services globally. The World Health Organisation (WHO) advocates for palliative care integration from the lower levels of the healthcare system. However, health systems in many low—and middle-income countries suffer from a lack of palliative care services at the lower level. This study aimed to explore the perceptions of the hospital in charge (the managers from 15 Health Centre facilities) on available healthcare services that can facilitate the integration of palliative care services at primary care facilities in Dar es Salaam, Tanzania. Methods and findings An exploratory qualitative case study on the perceptions of purposefully selected health facilities in charge of the available healthcare services, which can be used to facilitate the integration of palliative care services in primary care facilities. A semi-structured interview guide was used to conduct in-depth interviews with the selected informants. Data was analysed using a content analysis approach. Two categories emerged from the in-depth interviews: the availability of physical support services to manage pain and symptoms and multiple support systems to facilitate care for patients with chronic illnesses. Health facilities in charge consider the availability of various healthcare services at primary healthcare facilities essential for integrating palliative care services at this level. However, these services do not work in the context of palliative care and lack the philosophy behind it. Conclusion The availability of these services is a starting point for developing palliative care philosophy and, thus, its integration. Capacity building on palliative care services at the Primary health care facilities is recommended.